Pelatihan Fermentasi Daun Kering sebagai Alternatif Pakan Ternak di Desa Sumbung Kecamatan Cepogo Kabupaten Boyolali - Nur Fadila; Ari Wahyono; Amy Wulandari; Sumiyati Sumiyati; Lutvia Tribuwana; Tri Widianto; Suhendra Suhendra; Putri Nawang Asri; Diva Amelia Merryana Putri; David Kadar Saputro; Aditya Santoso; Joko Warsito (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Boyolali is known as a milk-producing city, which makes animal husbandry one of the biggest options for economic activity. Limited forage resources are one of the problems faced by breeders. This activity aims to provide fermentation training using dry leaves as an alternative animal feed. The method used is to collect dry leaves from local resources in Sumbung Village, followed by training on the fermentation process using probiotic bacteria, which has been proven to be effective in increasing the nutritional value of feed. Fermented dry leaves have an aroma and taste that livestock like, thereby increasing feed consumption. Utilizing fermented dried leaves as animal feed can be a sustainable solution for overcoming limited food sources in Sumbung Village. Apart from providing a higher-quality alternative feed, this research can also support efforts to manage dry leaf waste and encourage environmental sustainability.